Effect of living arrangements on cognitive function in Chinese elders: a longitudinal observational study. Issue 10 (6th October 2022) - Lin, Yanwei; Zhang, Qi; Wang, Tingxian; Zeng, Zhirong
Abstract : Objective: To examine how living arrangement as a social contextual factor can affect Chinese elders' cognitive function. Setting and participants: Our sample consists of 2486 Chinese elders from two waves (2014 and 2018) of the Chinese Longitudinal Healthy Longevity Survey (CLHLS) that was administered in 22 of China's 31 provinces using a multi-stage, disproportionate, purposive random sampling method. The CLHLS aims to better understand the determinants of healthy longevity in China and collects extensive data on a large population of fragile elders aged 80–112 in China. Outcome measures: Cognitive function was measured by the Mini-Mental State Examination (MMSE). Living arrangement was divided into living in an institution, living alone and living with household members. Generalised linear regressions were carried out to examine the associations between baseline characteristics and cognitive function, while controlling age, gender and residential area. Results: A total of 2486 participants were included in the study at baseline in 2014. Of these, 1162 (46.7%) were men and 1324 (53.3%) were women. The mean age at baseline was 75.07 (±8.31) years. The mean years of schooling were 2.86 (±3.68). The number (proportion) of the three living arrangements (lived in institutions, lived alone and lived with household members) were 93 (3.8%), 463 (18.6%) and 1930 (77.6%), respectively. Among all participants, cognitive function declined over time. Those who lived alone presented with the highest MMSE scores at baseline and showed the lowest decline after 4 years. Living arrangements had significant effects on decreasing cognitive function. Conclusion: Chinese elders living in institutions were most vulnerable to cognitive decline. Living alone was not a risk condition in itself for the elderly in terms of cognitive decline. In addition, the benefits of living with household members to support cognitive function were not found in our study.